Herpes virus in juvenile Pacific oysters Crassostrea gigas from Tomales Bay, California, coincides with summer mortality episodes - Friedman, CS; Estes, RM; Stokes, NA; Burge, CA; Hargove, JS; Barber, BJ; Elston, RA; Burreson, EM; Reece, Kimberly S (Diseases of Aquatic Organisms, 2005)
Pacific Crassostrea gigas and eastern C. virginica oysters were examined between June 2002 and April 2003 from 8 locations along the east, west and south USA coasts for oyster herpes virus (OsHV) infections using the A primer set in a previously developed PCR test. Only surviving Pacific oysters from a mortality event in Tomales Bay, California, USA, where annual losses of oysters have occurred each summer since 1993, were infected with a herpes-like virus in 2002. PCR examination using template amounts of both 50 and 500 ng were essential for OsHV detection. Sequence analysis indicated that the Tomales Bay OsHV was similar to that identified in France with the exception of a single base pair substitution in a 917 bp fragment of the viral genome. However, unlike the French OsHV-1, the Tomales Bay OsHV did not amplify with the primer pair of a second OsHV-1 PCR assay, suggesting that further characterization of these viruses is warranted. No evidence of Cowdry type A viral infections characteristic of herpes virus infections or other pathogens were observed in OsHV-infected oysters. Hemocytosis, diapedesis and hemocyte degeneration characterized by nuclear pycnosis and fragmentation were observed in infected oysters, which is consistent with previous observations of OsHV infections in France. Together these data suggest that OsHV may be associated with the annual summer Pacific oyster seed mortality observed in Tomales Bay, but establishment of a causal relationship warrants further investigation.